The ethics of refusing to care for patients during the coronavirus pandemic: A Chinese perspective. Issue 1 (21st September 2020) - Zhu, Junhong; Stone, Teresa; Petrini, Marcia
Abstract: As a result of the coronavirus (COVID‐19) pandemic, health professionals are faced with situations they have not previously encountered and are being forced to make difficult ethical decisions. As the first group to experience challenges of caring for patients with coronavirus, Chinese nurses endure heartbreak and face stressful moral dilemmas. In this opinion piece, we examine three related critical questions: Whether society has the right to require health professionals to risk their lives caring for patients; whether health professionals have the right to refuse to care for patients during the coronavirus pandemic; and what obligations there are to protect health professionals? Value of care, community expectations, legal obligations, professional and codes of practice may compel health professionals to put themselves at risks in emergency situations. The bioethical principles of autonomy, justice, beneficence and non‐maleficence, as well as public health ethics, guide nurses to justify their decisions as to whether they are entitled to refuse to treat COVID‐19 patients during the pandemic. We hope that the open discussion would support the international society in addressing similar ethical challenges in their respective situations during this public health crisis.